Pengaruh Kompetensi Dan Profesionalisme Terhadap Kinerja Pegawai Pada Dinas Pendidikan Pemuda Dan Olahraga Kota Bima - ST. Nurul Faturahman; Kartin Aprianti; Amirulmukminin Amirulmukminin (Universitas 17 Agustus 1945 Semarang, 2024)
Every agency generally expects employees to be able to carry out their duties effectively, efficiently, productively and professionally with the competencies they possess. This research aims to determine the influence of competence and professionalism on employee performance at the Bima City Youth and Sports Education Department. This research is associative research with a research sample of 45 respondents. The data collection technique uses a Likert scale questionnaire and the data analysis technique uses multiple linear regression analysis with the help of SPSS for Windows. The research results show that partially and simultaneously competence and professionalism have a significant influence on employee performance at the Bima City Education, Youth and Sports Department.